Investigation of operating parameters in a vertical stirred mill - Edwards, Garren Chad (Centre for Minerals Research, 2016)
Due to the depletion of coarser grained ores, more mineralogically complex ores are being treated. These complex ores usually have finer grained valuable minerals. Liberation of these finer grained valuable minerals lies in grinding finer. Grinding to these fine sizes is energy intensive and using standard ball mills are energy inefficient at these sizes (P80 < 75μm). Therefore, stirred mills are becoming increasingly prevalent in the mineral processing industry. In order to optimize these mills, the effects and mechanisms of the significant variables need to be understood. This project investigated operating parameters against performance in a laboratory scale vertical stirred mill (Deswik mill), in an ultrafine grinding (UFG) application of MG2 reef in the bushveld igneous complex. The operating variables that were investigated are stirrer speed, solids concentration, media size and media filling. The Kwade stress energy model was tested on the grinding results. The grinding performance was quantified in two ways, i.e. grinding efficiency and grinding rate. The grinding performance for this study was also investigated through a statistical analysis. The experiments was designed using a face centred central composite design (FCCD) and the results was statistically analysed using a design of experiments (DOE) software.